In vitro synergistic cytotoxic activity of oral hypoglycemic agent (Metformin) with Methotrexate against cancerous cells - Rizvi, Fatima (ADVANCES IN BASIC MEDICAL SCIENCES, 2025)
OBJECTIVE: Evaluation of synergistic cytotoxic effects of add-on therapy of Metformin with Methotrexate in different cancerous cells. METHODOLOGY: This interventional study was undertaken at BMSI, JPMC, in conjunction with PCMD. The trial lasted three months. To appraise the Cytotoxic activity of metformin only and in combination with methotrexate, we employed cells from breast cancer (MCF-7 and MDA-MB-231), vaginal cancer (Hela), and colorectal adenocarcinoma (HT-29 cell line). We employed the most appropriate MTT tests to assess cytotoxic effects. RESULTS: When the percentage viabilities of the examined cell lines were compared, it was discovered that combination therapies of Metformin and Methotrexate dramatically lowered the percentage viabilities and had synergistic cytotoxic effects. There was a significant difference in the percent viability of cells representing breast cancer (MCF-7, MDA-MB-231), colorectal carcinoma (HT-29), and vaginal carcinoma representative cells (Hela cell lines) as assessed by MTT assay between Metformin alone and Metformin with Methotrexate. CDI values of each cell line for combination therapy were 0.702 ± 0.034, 0.67 ± 0.019, 0.69 ± 0.019, and 0.73 ± 0.040 for MDA-231, Hela, MCF-7, and HT-29 cells, respectively. CONCLUSION: This research showed that Metformin also has synergistic effects with Methotrexate, in addition to having antiproliferative effects on the studied cancer cell lines.